Multigram Synthesis of Fluoroalkyl‐Substituted Pyrazole‐4‐carboxylic Acids. Issue 4 (22nd December 2014) - Iminov, Rustam T.; Mashkov, Alexander V.; Vyzir, Ivan I.; Chalyk, Bohdan A.; Tverdokhlebov, Anton V.; Mykhailiuk, Pavel K.; Babichenko, Ludmila N.; Tolmachev, Andrey A.; Volovenko, Yulian M.; Biitseva, Angelina; Shishkin, Oleg V.; Shishkina, Svetlana V.
Abstract: Acylation of tert ‐butyl 3‐(methylamino)but‐2‐enoate with fluorinated acetic acid anhydrides occurred at the enamine carbon atom. The reaction of the resulting tert ‐butyl 3‐(methylamino)‐2‐(RF CO)but‐2‐enoates with alkyl hydrazines resulted in mixtures of isomeric pyrazoles that were easily separated by column chromatography. The target fluorinated pyrazole‐4‐carboxylic acids were obtained on a multigram scale. Abstract : Fluorinated pyrazolecarboxylic acids ― potential building blocks for agrochemical applications ― have been prepared on a multigram scale. The easy separation of the isomeric mixture of esters was the key feature of the synthesis.